Aggressive Treatment of Refractory Coronary Artery Vasospasm in a Patient with Malignant Ventricular Tachyarrhythmia and Cardiac Arrest - Doğan, Mert; Kaya, Ergün Barış; Deniz, Çiğdem; Canpolat, Uğur; Şahiner, Mehmet Levent; Ateş, Ahmet Hakan; Aytemir, Kudret (European Journal of Therapeutics, 2023)
Coronary artery vasospasm (CAVS) is a clinical entity that can cause angina, but also unstable angina pectoris, acute myocardial infarction, fatal arrhythmias, and sudden death. Although it is a condition that is usually controlled with medical treatment, more aggressive treatments may rarely be required. In this case, the patient with a known diagnosis of CAVS had multiple arrests despite optimal medical treatment. We observed that fatal arrhythmias persisted in the Implantable Cardioverter Defibrillator (ICD) records, even though we implanted a stent and gave the patient maximal medical treatment. We performed sympathectomy as a last resort and we did not detect any recurrence in the 6-month follow-up of the patient. ICD implantation and sympathectomy should always be considered in resistant CAVS cases.